Isolasi Penghambat Aktivitas Enzim Pengubah Angiotensin Dari Protein Susu - Amhar Abubakar (Jurnal Agripet, 2007)
ABSTRACT. Three kinds of samles (whey protein containing casenoglycopeptide, whey protein removedcasenoglycopeptide and cheese whey powder digested with 7 kinds of proteases at 370C for 24 hr (trypsin, protenase-K, actinase-E, thermolysin, and papain) or 250C (pepsin and chymotrypsin). Strong inhibotory activity against the angiotensin converting enzyime (ACE, EC 3.4.15.1) was generated in all samples by 5 proteases digestion (pepsin, chymotrypsin, protinase-K, thermolysin and papain). In whey protein removed caseinoglycopeptide digestion by thermolysin induced the highest activity (95,25%). In cheese whey powder, the highest activity was derived by thermolysin (98.25%). On the other hand, week ACE inhibitory activity were derived by trypsin and actinase-E digestion. As no remarkable differences in inhibitory activity were observed between whey protein containingcasenoglycopeptideand whey protein removedcasenoglycopeptide samples, the bioactive peptides are considered to come mainly not fromcasenoglycopeptide but from cheese whey powder components.